Analyzing the Role of Board Independence towards Corporate Cash Holding: Evidence from Listed Family Firms of Emerging Economy - MENGYUN, WU; UM-E-HABIBA,; AKBAR, MUHAMMAD IMAD-UD-DIN; MEMON, MUHAMMAD ABDUL BASIT; HUSNAIN, MUHAMMAD (The journal of contemporary issues in business and government, 2021)
Family businesses are a valuable and well-known corporate name all over the world. However, controlling families have a clear incentive to obtain private benefits via asset expropriation from minority owners and to take activities that diminish the firms' value especially in emerging economies. A strong governance structure protects against these practices and affects long-term success by lowering them. This study adds to this scope by examining the effect of board independence, board size, leverage, dividend distribution, and company size on cash holding in the case of Pakistani listed family firms. Secondary data of sample of 212 family listed firm for the period of 2010-2017 from published annual reports and corporate governance reports are used. The static and dynamic models: fixed effect (F.E.), random effect (RE), and generalized method of moment (GMM) are the critical tools of evaluation in this study. Results show that board independence negatively affects cash holding, indicating that governance plays an active part in family businesses, whereas board size positively impacts cash holding, and demonstrating inefficient governance. Finally, study has policy guidelines for shareholders, and all other stakeholders.